Inhibition of sodium‐glucose cotransporter 2 ameliorates renal injury in a novel medaka model of nonalcoholic steatohepatitis‐related kidney disease. Issue 12 (1st November 2019) - Nagoya, Takuro; Kamimura, Kenya; Goto, Ryo; Shinagawa‐Kobayashi, Yoko; Niwa, Yusuke; Kimura, Atsushi; Sakai, Norihiro; Ko, Masayoshi; Nishina, Hiroshi; Terai, Shuji
Abstract : The effect of sodium‐glucose cotransporter 2 inhibitor (SGLT2I) on nonalcoholic steatohepatitis (NASH) has been reported, but there are few studies on its effect on NASH‐related renal injury. In this study, we examined the effect of SGLT2I using a novel medaka fish model of NASH‐related kidney disease, which was developed by feeding the d‐rR/Tokyo strain a high‐fat diet. SGLT2I was administered by dissolving it in water of the feeding tank. SGLT2I ameliorates macrophage accumulation and oxidative stress and maintained mitochondrial function in the kidney. The results demonstrate the effect of SGLT2I on NASH‐related renal injury and the usefulness of this novel animal model for research into NASH‐related complications. Abstract : Here, we demonstrate that the highly specific sodium‐glucose cotransporter 2 inhibitor (SGLT2I) prevented the progression of nonalcoholic steatohepatitis (NASH)‐related renal injury in a medaka fish model of NASH‐related kidney disease. SGLT2I ameliorates oxidative stress and macrophage accumulation and maintained mitochondrial function in renal tubules.